Proceedings of the 13th Conference on "Data analysis methods for software systems - Bernatavičienė , Jolita (Vilnius University Proceedings, 2022)
DAMSS-2022 is the 13th International Conference on Data Analysis Methods for Software Systems, held in Druskininkai, Lithuania. Every year at the same place and time. The exception was in 2020, when the world was gripped by the Covid-19 pandemic and the movement of people was severely restricted. After a year’s break, the conference is back on track. 2021 conference was successful, and the main objective of lively scientific communication was again achieved. The conference focuses on live interaction among participants, but there is also some scope for a limited number of virtual presentations. For better efficiency of communication among participants, most of the presentations are poster presentations. This format is really effective.The history of the conference goes back to 2009, when 16 papers were delivered. It started as a workshop and has now grown into a well-known conference. The idea of such workshop was conceived at the Institute of Mathematics and Informatics, which is now the Institute of Data Science and Digital Technologies of Vilnius University. The Lithuanian Academy of Sciences and the Lithuanian Computer Society supported this idea. This idea has been welcomed by the Lithuanian scientific community and abroad. The number of this year’s presentations is 81. The number of registered participants is 121 from 10 countries. This is significantly more than in 2021. The conference brings together researchers from six Lithuanian universities. This makes the conference the main annual meeting point for Lithuanian computer scientists. The main goal of the conference is to introduce the research undertaken at Lithuanian and foreign universities in the fields of data science and software engineering. The annual organization of the conference allows the fast interchanging of new ideas among the scientific community. Seven IT companies supported the conference this year. This means that the topics of the conference are actual for business, too.Topics of the conference cover Artificial Intelligence, Big Data, Bioinformatics, Blockchain Technologies, Business Rules Software Engineering, Data Science, Deep Learning, Digital Technologies, High-Performance Computing, Machine Learning, Medical Informatics, Modelling Educational Data, Ontological Engineering, Optimization in Data Science, Signal Processing, Visualization Methods for Multidimensional Data. This book gives an overview of all presentations of DAMSS-2022 conference.